2011
DOI: 10.1007/s00180-011-0256-2
|View full text |Cite
|
Sign up to set email alerts
|

Empirical properties of forecasts with the functional autoregressive model

Abstract: We study the finite sample performance of predictors in the functional (Hilbertian) autoregressive model X n+1 = Ψ(X n ) + ε n . Our extensive empirical study based on simulated and real data reveals that predictors of the formΨ(X n ) are practically optimal in a sense that their prediction errors are comparable with those of the infeasible perfect predictor Ψ(X n ). The predictionsΨ(X n ) cannot be improved by an improved estimation of Ψ , nor by a more refined prediction approach which uses predictive factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 15 publications
1
42
1
Order By: Relevance
“…location and or scale. Similarly as Horváth et al (2014) and Didericksen et al (2012) we considered samples with functional errors being generated by Wiener process and Brownian bridge divided into 1440 and 120 time points (24 hours divided into 1min and 12min time segments). We considered samples of equal and different sizes.…”
Section: Properties Of the Proposals -Simulation Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…location and or scale. Similarly as Horváth et al (2014) and Didericksen et al (2012) we considered samples with functional errors being generated by Wiener process and Brownian bridge divided into 1440 and 120 time points (24 hours divided into 1min and 12min time segments). We considered samples of equal and different sizes.…”
Section: Properties Of the Proposals -Simulation Studiesmentioning
confidence: 99%
“…. , N. We used the following (Didericksen et al, 2012) designs of a simulation study. (5) under alternative in which the first sample is generated from population related to fig.…”
Section: Properties Of the Proposals -Simulation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictive factors are interesting in that they are functions which can be used to expand the curves, very much like the FPCs are used, but they define directions in the space L 2 which are most relevant for prediction. Using a finite sample implementation, Didericksen et al 43 found that it does not lead to more accurate predictions. In general, predicted curves that use formula 3.10 tend to be closer to the mean curve and smoother than the actual observations.…”
Section: Predictionmentioning
confidence: 99%